CORRELATION OF DIABETES REMISSION WITH REDUCTIONS IN BLOOD PRESSURE AND CARDIOVASCULAR RISK SCORES: RESULTS OF SIX MONTHS OF RANDOMISED TRIAL WITH DIGITAL TWIN TECHNOLOGY. (June 2022) - Shamanna, Paramesh; Joshi, Shashank; Shah, Lisa; Dharmalingam, Mala; Vadavi, Arun; Damodaran, Suresh; Mohammed, Jahangir; Mohamed, Maluk; Poon, Terrence; Keshavamurthy, Ashok; Thajudeen, Mohamed; Bhonsley, Suchitra
Abstract : Objective: Twin precision treatment improves metabolic parameters using a whole-body digital twin platform powered by artificial intelligence and internet of things Design and method: We evaluated 6 month data of RCCT (n = 128). Diabetes remission was defined as HbA1c < 6.5% for at least 3 months without Anti-Diabetic Medication (ADM) Results: Mean age and duration of diabetes (yrs) was 43 (±9.4, 95% CI 42 to 45) and 3.5 (±2.7, 95% CI 3 to 4). 88.3% (n = 113) achieved diabetes remission. At enrolment 76% (n = 97) were on ADM, of which 90% (n = 87) were off ADM. There was a significant change (change, % reduction) in HbA1c % (8.9 to 5.6, -38.2), SBP mmHg (128 to 118, -8.5), DBP mmHg (84 to 78, -7.8), waist circumference cm (97 to 86, -11.2), body weight kg (78 to 67, -12.7), BMI (27.2 to 23.5, -13.6), HOMA2IR (1.9 to 1.02, -48.4), Framingham Risk Score (FRS) (15.4 to 6.6, -56.4), Atherosclerotic Cardiovascular Disease (ASCVD) (7.9 to 3.1, -60.7), [p < 0.0001], QRISK3 (12.8 to 9.3, -27.3) scores, [p = 0.0027], at six months. (Table). There was a significant positive correlation between HbA1c reduction, and reductions in SBP (r 0.2, 95% CI 0.03 to 0.36, p = 0.03), HOMA2IR (r 0.23, 95% CI 0.06 to 0.39, p = 0.0074), ASCVD (r -0.17, 95% CI 0.004 to 0.34, p = 0.04), FRS (r 0.22, 95% CI 0.056 to 0.38, p = 0.0097). 57% (n = 73) were hypertensives. At 6 month, 33% (n = 6/18) were off anti-hypertensive medication Conclusions: Digital twin technology enables a significant reduction in BP, CV risk scores and insulin resistance which correlates with the remission of T2DM